Corona phobia and mental health among nurses: identifying determinants in a cross-sectional survey - Yildirim, Menevse; Yildiz, Emre; Seren Intepeler, Seyda (Frontiers in Public Health, 2025)
BackgroundAssessing the psychological impact of the pandemic on nurses is essential for protecting their well-being and ensuring the resilience of healthcare systems.MethodsA descriptive, cross-sectional study following the STROBE reporting guidelines. The study included 417 nurses from Dokuz Eylul University Research and Practice Hospital who participated voluntarily. Data were collected between July and October 2021 using the Sociodemographic Data Form, the COVID-19 Phobia Scale (C19P-S), and the Mental Health Continuum Short Form (MHC-SF). Descriptive statistics and multiple linear regression analysis were used (p < 0.05).ResultsThe mean C19P-S score was 49.03 ± 17.29. Gender, education, perceived general health status, and intention to quit predicted 17% of COVID-19 phobia variance (R2 = 0.17, p < 0.05). The mean MHC-SF score was 34.31 ± 16.53. Categorically, 46.8% of nurses were languishing in the emotional subdimension, 42.4% were mentally healthy, and 25% were languishing in social and psychological well-being.ConclusionNurses experienced moderate COVID-19 phobia, with female gender, undergraduate education, worse perceived health, and intention to quit emerging as significant predictors, collectively explaining 17% of the variance. Interventions are needed to strengthen nurses’ mental health, particularly emotional well-being. Healthcare policymakers and administrators should implement strategies to support nurses’ psychological well-being and foster a fear-free work environment through empowerment.